Obesity is associated with larger soft‐tissue sarcomas, more surgical complications, and more complex wound closures (obesity leads to larger soft‐tissue sarcomas). Issue 1 (7th June 2018) - Montgomery, Corey; Harris, John; Siegel, Eric; Suva, Larry; Wilson, Margaret; Morell, Sean; Nicholas, Richard
Abstract : Background and Objectives: Does a link exist between obesity and soft‐tissue sarcoma outcomes? We hypothesized that soft‐tissue sarcomas in patients with obesity may lead to larger tumors at detection, with an increased risk for a more complex surgical excision, wound healing‐related complications, higher stage at presentation, and decreased survival. Methods: One hundred thirty‐nine and patients with soft‐tissue sarcoma were retrospectively evaluated over 10 years. Patients were divided into 2 cohorts based on the World Health Organization body mass index (BMI) obesity grouping. A BMI ≥ 30 kg/m 2 was classified as obese and a BMI < 30 kg/m 2 was classified as nonobese. Results: Eighty‐five nonobese and 54 obese individuals were evaluated. The median tumor diameter was 50% larger ( P  = .024) and the overall complication rate was 1.7‐fold higher in patients with obesity ( P  = .0032). Patients with obesity also had a statistically significantly higher rate of complex wound closures. In multivariable logistic regression, obesity remained a highly significant factor favoring complications after the surgical treatment of soft‐tissue sarcoma (odds ratio = 3.66, 95% confidence interval = 1.54‐8.71; P  = .0033). No statistically significant differences were noted on comparing groups for the incidence of metastatic spread or survival. Conclusions: These findings suggest that obesity is associated with larger tumors, a higher incidence of wound complications, and greater use of complex wound‐closure methods.